An Efficient Method for Adventitious Root Induction from Stem Segments of Brassica Species - Srikanth, Sandhya; Choong, Tsui Wei; Yan, An; He, Jie; Chen, Zhong (Frontiers in Plant Science, 2016)
Plant propagation via in vitro culture is a very laborious and time-consuming process. The growth cycle of some of the crop species is slow even in the field and the consistent commercial production is hard to maintain. Enhanced methods of reduced cost, materials and labor significantly impact the research and commercial production of field crops. In our studies, stem-segment explants of Brassica species were found to generate adventitious roots (AR) in aeroponic systems in less than a week. As such, the efficiency of rooting from stem explants of six cultivar varieties of Brassica spp was tested without using any plant hormones. New roots and shoots were developed from Brassica alboglabra (Kai Lan), B. oleracea var. acephala (purple kale), B. rapa L. ssp. chinensis L (Pai Tsai, Nai Bai C, and Nai Bai T) explants after 3 to 5 days of growing under 20 ± 2°C cool root zone temperature (C-RZT) and 4 to 7 days in 30 ± 2°C ambient root zone temperature (A-RZT). At the base of cut end, anticlinal and periclinal divisions of the cambial cells resulted in secondary xylem toward pith and secondary phloem toward cortex. The continuing mitotic activity of phloem parenchyma cells led to a ring of conspicuous white callus. Root initials formed from the callus which in turn developed into ARs. However, B. rapa var. nipposinica (Mizuna) explants were only able to root in C-RZT. All rooted explants were able to develop into whole plants, with higher biomass obtained from plants that grown in C-RZT. Moreover, explants from both RZTs produced higher biomass than plants grown from seeds (control plants). Rooting efficiency was affected by RZTs and explant cuttings of donor plants. Photosynthetic CO2 assimilation rate (Asat) and stomatal conductance (gssat) were significantly differentiated between plants derived from seeds and explants at both RZTs. All plants in A-RZT had highest transpiration rates.